Gas-phase domino cyclization of phosphonium ylides leading to the total synthesis of Eustifoline D. Issue 46 (15th November 2017) - Aitken, R. Alan; Murray, Lorna
Graphical abstract: Highlights: Six different stabilised phosphorus ylides suitable for cascade cyclization have been prepared. Pyrolysis mainly gives styrylquinolines accompanied by other fused-ring quinolines and carbazoles. With a ring methyl present the quinoline is accompanied by the furocarbazole natural product Eustifoline D. Eustifoline D is formed in 5 steps from 5-methylanthranilic acid. Abstract: Six stabilised phosphonium ylides bearing ortho -benzylaminophenyl and cinnamoyl (or a heterocyclic analogue) groups have been prepared and upon flash vacuum pyrolysis at 800 °C were found to undergo cascade cyclization processes to give mainly 3-styrylquinolines but also in some cases ring-fused carbazoles and other fused-ring heterocyclic products. By starting with an appropriate ring-methylated precursor the natural product Eustifoline D was obtained in 19% yield in the pyrolysis in addition to the 3-(2-furylethenyl)quinoline (46%).